2016
DOI: 10.18632/oncotarget.11978
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy between concurrent chemoradiotherapy with or without adjuvant chemotherapy and intensity-modulated radiotherapy alone for stage II nasopharyngeal carcinoma

Abstract: ObjectiveThis study aimed to explore whether concurrent chemoradiotherapy (CCRT) with or without Adjuvant Chemotherapy (AC) could improved the survival in stage II nasopharyngeal carcinoma (NPC).MethodsPatients with stage II NPC treated with CCRT (n=80) or CCRT+AC (n=40) or IMRT alone (n=42) between January 2007 and September 2014 were retrospectively analyzed. The three patient groups were matched based on prognostic factors. All patients were treated with IMRT. The endpoints were overall survival (OS), dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…Moreover, a multi-center study suggested that CCRT improved 5-year LRFS and progression-free survival [ 32 ]. However, several retrospective cohort studies showed that IMRT alone was a reasonable option for stage II NPC whereas, in line with the present results, chemotherapy use failed to improve survival [ 10 12 , 15 17 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, a multi-center study suggested that CCRT improved 5-year LRFS and progression-free survival [ 32 ]. However, several retrospective cohort studies showed that IMRT alone was a reasonable option for stage II NPC whereas, in line with the present results, chemotherapy use failed to improve survival [ 10 12 , 15 17 ].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, no differences were found between subgroups in 5-year LRFS and OS. Of note, several studies showed similar results [ 10 , 11 , 14 , 15 ]. Yet, despite much evidence that chemotherapy did not improve survival of stage II NPC, it was still widely used in clinical practices.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, an accurate staging system helps clinicians not only predicting prognoses, but also making treatment decisions. Recently, several studies have demonstrated that no survival benefits are found from the additional concurrent chemotherapy to NPC with stage Ⅱ disease[1719]. Therefore, after comparing the two schemes of the new T stage system, we recommend that it may be better to merge the current T2 and T1 categories into the new T1 stage.…”
Section: Discussionmentioning
confidence: 99%
“…The Kaplan-Meier survival curves showed no significant difference in OS (P=0.200), LRFS (P=0.204), or DMFS (P=0.064) in patients treated with RT alone, CCRT, or CCRT + AC. And Chen et al 27 demonstrated a similar result.…”
Section: Adjuvant or Induction Chemotherapy Combined With Imrt For Stmentioning
confidence: 73%